Formulation and Evaluation of Supersaturable Self Nano-Emulsifying Drug Delivery System of Poorly Water Soluble Atorvastatin Calcium - Tarkase, K N; Damale, P S; Kapare, P S; Lagad, V A (Asian Journal of Pharmaceutical Research and Development, 2014)
The SSNEDDS approach is to generate a protracted supersaturated solution of the drug when the formulation is released from an appropriate dosage form into an aqueous medium. Surpersaturation is intended to increase the thermodynamic activity to the drug beyond its solubility limit and, therefore, to result in an increased driving force for transit into and across the biological barrier. The drug will be solubilized in the GI tract in oil droplets, the large amount and small size of which lead to a considerable increase of surface area from where drug dissolution can take place. SNEDDS can enhance drug absorption by a number of ancillary mechanisms, including reduction of gastric motility and alteration of the physical and biochemical barrier function of the gastro-intestinal mucosa. Supersaturable SEDDS formulations differ from the conventional SEDDS formulations as they contain a reduced amount of surfactant and a polymeric precipitation inhibitor.